An Improved Analytical Approach for Segmental Joint Rotational Behavior Considering the Elastic Gasket - Ming Huang; Fan Yang (Applied Sciences, 2022)
To fully consider the effect of elastic gasket (EG) on the segmental joint rotational behavior, an improved analytical approach is proposed to simulate the joint rotations and obtain the rotational stiffnesses. By comparing the analytical results with the experimental results and numerical results, the joint compression zone should be simulated by the concrete–EG–concrete (CGC) model instead of rigid–EG–rigid (RGR) model or concrete–concrete (CC) model. Since the analytical approach with the CGC model can simulate the combined work of EG and concrete well, it is a more effective approach to obtain the joint rotational stiffnesses. According to these analytical results, the EG has a great impact on softening the joint rotations, and this leads the rotational stiffnesses of the joint with EG to be evidently smaller than those of the joint without EG. In addition, with decreasing the axial force or increasing the EG thickness, this softening effect tends to be more obvious. Therefore, the EG is a significant factor which should be fully considered during the theoretical analysis for the joint rotation behavior, or it may lead to an unreliable design for the segmental lining.